2017
DOI: 10.2965/jswe.40.21
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Method for Measuring of Sediment Oxygen Demand in Lakes and Its Application

Abstract: In this study, we developed a new measurement method of sediment oxygen demand (SOD) . SOD in the bottom layer of lakes is closely related to the change in dissolved oxygen (DO) which is to be a new environmental standard for aquatic environments. Our method makes use of undisturbed sediment cores and measures SOD more easily and faster than the existing methods. Since the instruments are portable, our method can be widely applied to many lakes. SOD measurements in Lake Kasumigaura and Lake Biwa (the northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…To clarify the factors affecting DO consumption of the new method, we examined the reason for the slight difference in SOD found between the stirring vial and core methods. Although there was a difference in the amount of sediments collected in the vessel used for the core and vial methods, Shimotori et al (2017) showed that the amount of sediment collected in the SOD vial did not affect the measurement results. Therefore, the difference between the core and stirring vial methods can be verified by focusing on the effect of the water velocity in the vessel and the content of benthic organisms.…”
Section: Comparison With the Conventional Core Methodsmentioning
confidence: 94%
“…To clarify the factors affecting DO consumption of the new method, we examined the reason for the slight difference in SOD found between the stirring vial and core methods. Although there was a difference in the amount of sediments collected in the vessel used for the core and vial methods, Shimotori et al (2017) showed that the amount of sediment collected in the SOD vial did not affect the measurement results. Therefore, the difference between the core and stirring vial methods can be verified by focusing on the effect of the water velocity in the vessel and the content of benthic organisms.…”
Section: Comparison With the Conventional Core Methodsmentioning
confidence: 94%